Gen-X vs Gen-Y: How They Perceive Work-Life Balance? - Ng, Le Chiak; Dayang Kartini, Abang Ibrahim (-, 2012)
Work-life balance is a newly discussed issue in Malaysia. Therefore, study needs to be done to understand the work-life balance issues in Malaysia. This study is to find out how work-life balance is being perceived among the Malaysians, especially generation X and generation Y. In this study, 2 generation X and 2 generation Y have been chosen as the informant. The samples are chosen by using purposive sampling method. Data collection has been carried out with the 4 informants by using semi-structured interview. Then, the data collected is analysed using content analysis. Findings from the data collection suggested that generation X and generation Y understand work-life balance as an involvement balance in work and life, fulfilling the responsibility in work and life, and both work and life need to be separated. Besides, findings also show that imbalance in work-life would lead to many impacts which the most significant impact is turnover intention. Therefore, there is a need in addressing work-life balance issue by government or organization. Informants suggested 21 initiatives which can be taken to help the employees in achieving work-life balance which includes increase management awareness on work-life balance, introduce teleworking, organize recreation activity and awareness program on work-life balance, and create a family-friendly organization. In term of the challenges in achieving work-life balance, different informant has mentioned different challenges whereby most of the challenges are related to individual factors. As overall, this study contributes to deeper understanding on work-life balance issues in Malaysia. Initiatives mentioned can become the guideline for the government or practitioners in addressing the work-life balance issues. Moreover, due to most of the research are done in western context, this study which is done in eastern context could serve as one of the important references for the furture reseach on work-life balance in eastern countries.